Curious Case of a Child with Wilson Disease: A Case Report (One Health Journal of Nepal, 2023)
Wilson disease is an autosomal recessive disorder occurs due to lack or dysfunction of transmembrane copper- transporting ATPase, causing accumulation of copper in liver, the nervous system, corneas, kidneys, and heart. Patient was asymptomatic at presentation even with the sign of Kayser Fleischer ring in the eye. Asymptomatic presentation of disease can have symmetric T2 and FLAIR high signal intensities in bilateral putamina in early age and absent T1 low signal intensity in these areas of the brain. Hence MRI needs to be done early to determine the disease early without considering age and symptom.Early finding of deposition of copper in brain without neurological presentation and abnormal Liver Function Test is rare and D-Penicillamine and Zinc was enough to decrease the progression of disease.